2018
DOI: 10.1002/ar.23983
|View full text |Cite
|
Sign up to set email alerts
|

Collateral Projections from the Lateral Parabrachial Nucleus to the Central Amygdaloid Nucleus and the Ventral Tegmental Area in the Rat

Abstract: Lateral parabrachial nucleus (LPB) is a critical region in the integration and transmission of peripheral nociceptive information. The parabrachio‐amygdaloid (P‐Amy) pathway and parabrachio‐ventral tegmental area (P‐VTA) pathway is thought to be significant in regulation of pain‐related negative emotions. In present study, retrograde tract tracers Fluoro‐gold (FG) and tetramethylrhodramine‐dextran (TMR) were stereotaxically injected into the right central amygdaloid nucleus (CeA) and right VTA, respectively. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…To demonstrate the reliability of our methodology, we showed the GFP-positive neurons and tdTomato-positive neurons in the LPB, a brain region containing common upstream input neurons to both the CeA and the VTA (Supplementary Figures S2G,H; Han et al, 2015;Qiao et al, 2019). Compared to the known brain regions that contain neurons projecting to the CeA, e.g., the medial prefrontal cortex (mPFC), the ventromedial hypothalamic nucleus (VMH), the dorsal raphe (DR), the paraventricular nucleus of the thalamus (PVT), the anterolateral part of BNST (alBNST), and the insular cortex (IC; Gungor and Pare, 2016;Ren et al, 2018;Lo et al, 2019;Keyes et al, 2020;Chen et al, 2021;Ma et al, 2021;Wang et al, 2022), we observed a similar pattern of the CeA-projecting tdTomato-positive neurons in the mPFC, the IC, the alBNST, the PVT, the VMH, and the DR in our study (Supplementary Figures S2A-F).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To demonstrate the reliability of our methodology, we showed the GFP-positive neurons and tdTomato-positive neurons in the LPB, a brain region containing common upstream input neurons to both the CeA and the VTA (Supplementary Figures S2G,H; Han et al, 2015;Qiao et al, 2019). Compared to the known brain regions that contain neurons projecting to the CeA, e.g., the medial prefrontal cortex (mPFC), the ventromedial hypothalamic nucleus (VMH), the dorsal raphe (DR), the paraventricular nucleus of the thalamus (PVT), the anterolateral part of BNST (alBNST), and the insular cortex (IC; Gungor and Pare, 2016;Ren et al, 2018;Lo et al, 2019;Keyes et al, 2020;Chen et al, 2021;Ma et al, 2021;Wang et al, 2022), we observed a similar pattern of the CeA-projecting tdTomato-positive neurons in the mPFC, the IC, the alBNST, the PVT, the VMH, and the DR in our study (Supplementary Figures S2A-F).…”
Section: Resultsmentioning
confidence: 99%
“…As the CeA and VTA are both critical brain regions involved in emotional regulation with nearly opposite functions, we were curious whether these regions share any common upstream inputs. Considering the existence that a population of calcitonin gene-related peptide (CGRP) neurons in the lateral parabrachial nucleus (LPB) innervating both the CeA and the VTA (Han et al, 2015;Qiao et al, 2019), we suspected that there might be other brain regions also containing neurons that innervated both the CeA and the VTA. Thus, it is interesting to investigate the existence of such common upstream inputs and the emotional valences they encode.…”
Section: Introductionmentioning
confidence: 99%
“…In the NP model, enhanced activity of LPB neurons is associated with a decrease in inhibitory GABAergic input, and activation of this pathway inhibits pain behavior ( Raver et al, 2020 ). In addition, LPB neurons can also transmit nociceptive information ( Liang et al, 2016 ) and negative emotions ( Qiao et al, 2019 ) to CeA. In the SNL model, LPB-CeA potentials significantly increase and manifest as abnormal tactile pain ( Nakao et al, 2012 ).…”
Section: Np-related Brain Nuclei and Neural Circuitsmentioning
confidence: 99%
“…The central amygdala (CeA) is the main nucleus that receive the outputs from LPB (5, 6), and consists of around 95% GABA neurons (CeA GABA ) (7). The neural circuits between LPB and CeA (LPB-CeA) has been implicated in the process of reward and addiction (1, 8-10), while most of these studies focus on the glutamatergic projections from calcitonin gene-related peptide (CGRP)positive neurons in the LPB to CeA (2,11,12). Here, we found a novel cholinergic projection from LPB to CeA, in which ChAT-positive neurons are mainly located in external portion of LPB (eLPB, Fig.…”
mentioning
confidence: 99%